Crystal structure of a DNA·RNA hybrid duplex with a polypurine RNA r(gaagaagag) and a complementary polypyrimidine DNA d(CTCTTCTTC) - Xiong, Yong (Oxford University Press, 2000)
DNA·RNA hybrid duplexes are substrates of RNase H and reverse transcriptase. The crystal structure of a hybrid duplex, d(5′-CTCTTCTTC-3′)·r(5′-gaagaagag-3′) (the uppercase letters indicate DNA and lowercase letters RNA), with a polypurine RNA strand and a complementary DNA strand has been determined at 1.8 Å resolution. The structure was refined first at 1.9 Å by XPLOR and subsequently by CNS at 1.8 Å. The hybrid is found in a standard A-form conformation with all the sugars in the C3′-endo puckering. The 5′-terminal base dC of the DNA strand was clearly visible in the electron density map of the present structure, in contrast to the previously reported structure d(TTCTTBr(5)CTTC)·r(gaagaagaa) where the 5′-terminal base dT was not visible, leaving the terminal rA unpaired. Thus, the comparison of the terminal base pairs, C·g versus T·a, in the two hybrid crystal structures provides information on the stability of these base pairs in hydrogen bonding (three versus two) and base stacking interactions. The differences in the terminal base pairs produce different kinks in the two structures. Minor groove widening is observed in the present structure at a distinctive kink in the lower half of the duplex, in contrast to the small widening of the minor groove and a very slight bend in the upper half of the T·a structure.